Electroless plating of nickel-phosphorous on surface-modified poly(ethylene terephthalate) films - Lima Jr. E. (2003)
Chemical surface preparation for Ni-P electroless metallization of poly(ethylene terephthalate) (PET) films without using Chromium-based chemicals, was studied. The applicability of this method was verified by a subsequent metallization process. Thermal analysis was conducted to observe the main thermal transitions and stability of the polymer and metallized films. Contact angle analysis was performed to assess the surface hydrophilicity so as to optimize the substrate preparation process. X-ray diffraction, EDAX and SEM analysis were used to understand the composition and morphology of the polymeric substrate and Ni-P coat growing process. Adherence strength, contact sheet resistivity and optical diffuse reflection were measured on the metallized films. The time of chemical etching affects the polymer surface hydrophilicity, polymer/metal adherence strength, surface resistance and optical diffuse reflection, while Ni coating morphology is controlled by the pH of the electroless bath. High wettability of the polymer surface, adherence strength of 800 N cm -2 , high optical diffuse reflection and low surface resistivity of the Ni coating, were found for films etched for 60 min. Metallizations performed at pH 7.5 produce Ni-P coatings with 12.0 wt.% phosphorous content, which were amorphous and flexible. The contact sheet resistivity of the plated films is sensitive to roughness variations of the substrate. The method proposed in this work allows the production of metallized films appropriate for the fabrication of flexible circuits. © 2003 Elsevier B.V. All rights reserved.